The Assessment of Writing Skill English Students’ at University - Manihuruk, Leonita Maria Efipanias; Esti Marlina Sirait (Institut Agama Islam Negeri Palopo, 2024)
This research aimed to analyze how the assessment of writing skill English students’ at University of HKBP Nommensen Pematangsiantar. This research was carried out at UHKBPNP. The researchers used qualitative approach with case study method. The subject of this research is 2th semester students of UHKBPNP, with consist of 25 students. The research design of this research was qualitative approach with case study method. The instrument of collecting data used writing test. The findings of the research: (1) Content aspect score was 16,52; (2) Organization aspect score was 15,4; (3) Vocabulary aspect score was 15,48; (4) Language use aspect score was 15,64; (5) Mechanics aspect score was 15,68. The result of the research showed that the students experienced mostly in excellent to very good level